Decision‐making in rectal surgery. (March 2014) - MacDermid, E.; Young, C. J.; Young, J.; Solomon, M.
Abstract Aim The decision to create a stoma after anterior resection has significant consequences. Decisions under uncertainty are made with a variety of cognitive tools, or heuristics. Past experience has been shown to be a powerful heuristic in other domains. Our aim was to identify whether the misfortune of recent anastomotic leakage or surgeon propensity to take everyday risks would affect their decision to defunction a range of anastomoses. Method Questionnaires were sent to members of the Colorectal Surgical Society of Australia and New Zealand. Participants were asked for demographic information, questions regarding risk‐taking propensity, when their last anastomotic leakage occurred and whether they would defunction a range of hypothetical rectal anastomoses grouped according to height, American Society of Anesthesiologists grade and use of preoperative radiotherapy. Scores were derived for hypothetical patient likelihood of having a stoma created and individual surgeon propensity for stoma formation. Hazard regression analysis was used to assess demographic predictors of stoma formation. Results In total, 110 (75.3%) of 146 surveyed surgeons replied; 72 (65.5%) reported anastomotic leakage within the last 12 months. Surgeons' propensity for risk‐taking was comparable (24.6 vs 27.53, 95% confidence interval, Mann–Whitney‐U) to previously studied participants in economic models. Surgeon age (< 50 years) and lower propensity for risk‐taking were demonstrated to be independent predictors of stoma formation on regression analysis. Conclusion Although the decision to create a stoma after anterior resection may be made in the belief that its foundation derives from rational thought, it appears that other unrecognized operator factors such as age and risk‐taking exert an effect.